Stylistic marks axiology in the “Explanatory dictionary of the Russian language” edited by D.N. Ushakov and the new lexicographic reality - Tatyana V. Markelova; Marina L. Novikova (Russian Language Studies)
The importance of addressing both theoretical and practical challenges of lexicography in the process of mastering, accumulating, and transmitting knowledge, which is materialized in language, is unquestionable. The relevance of the study is fueled by the enduring interest of researchers in the problems associated with developing academic traditions of Russian lexicography. The aim of the study is axiological analysis of stylistic markers, an important component of the lexicography metalanguage, and their systematization, which forms a methodological basis for further scholarly work in this field. This is because the research is based on the lexicographic tradition established by the prominent linguist D.N. Ushakov in the normative academic “Explanatory Dictionary of the Russian Language” (1935-1940), a harmonious and sequential approach to the lexicographic parameterization of the Russian language, characterizing the stylistic status of words. The methodology of comprehensive research included general scientific methods of observation, comparison, analysis, and the contextual method in assessing stylistic deviations of normative stylistic markers. The consistent idea in the study is that the results of the conducted research testify to the foresight of D.N. Ushakov as a linguist, who anticipated the development of axiological issues in Russian language studies and the special role of stylistic qualification of words, their close connection with the evaluative nature of words in negative and positive semantics. The prospects for studying the system of stylistic markers as an important component of lexicography metalanguage are clear; they highlight the position of the word in the system of literary language, its expressiveevaluative connotations. The modern picture of studying the stylistic stratification of the lexicon remains a significant research object at the current stage of the Russian language in the diversity of prospective methods of lexicographic stylistics.